TRAITEMENT DES EAUX COLOREES EN MILIEUX HOMOGENE ET HETEROGENE. - Abdelkader Khadraoui (My University, 2024)
Congo red dye is a chemical compound characterised by its azo (-N=N-) chromophore functional group. It is used in various fields, for example, in the dyeing of leather, fur, paper, and in the spinning bath of chemical fibres. This type of dye is a persistent pollutant, non-biodegradable, and recalcitrant. This work aims to degrade this azo dye using advanced oxidation processes, specifically Heterogenous Fenton and Sono-Fenton processes, under the influence of certain parameters such as the initial pH of the solution, the amount of the pollutant "Congo Red," the mass of iron, the concentration of H₂O₂, and temperature. The influence of ultrasound on the acceleration of the degradation of this substance was monitored by UV/visible spectrophotometry, and the best results were obtained using the (Fe2+/US/H₂O₂) process for the degradation of Congo Red. -------------------------------------------------------------------------------------- صبغة الكونغو الحمراء هي مركب كيميائي يتميز بمجموعة وظيفية آزو ] N = N [ الكروموفور تسُتخدم هذه الصبغة في عدة مجالات مثل صباغة الجلود، الفراء، الورق، وحمامات الغزل للألياف الكيميائية هذا النوع من الأصباغ يعتبر من الملوثات المستدامة والمقاومة غير القابلة للتحلل البيولوجي . تهدف هذه الدراسة إلى تحلل هذه الصبغة الآزوئية باستخدام عمليات الأكسدة المتقدمة Fenton ، تحت تأثير بعض العوامل مثل تركيز درجة الحموضة الابتدائية للمحلول، كمية الملون " الكونغو الحمراء " ، كمية الحديد، تركيز H₂O₂ ودرجة الحرارة، بالإضافة إلى تأثير الموجات فوق الصوتية على تسريع عملية التحلل . تم متابعة عملية التحلل باستخدام مطياف الأشعة فوق البنفسجية / المرئية، حيث تم الحصول على أفضل النتائج باستخدام عملية (Fe2+/US/H₂O₂ ------------------------------------------------------------------------------------- Le colorant Rouge Congo est un composé chimique qui est caractérisé par son groupement fonctionnel azo (-N=N-) chromophore. Il est utilisé dans plusieurs domaines à titre d’exemple (la teinture du cuir, de la fourrure, du papier, et du bain de filage des fibres chimiques) Ce type de colorants est des polluants persistants, non biodégradables et récalcitrants. Ce travail consiste à dégrader ce colorant azoïque par les procédés d’oxydation avancée Fenton Hétérogène et Sono Fenton Hétérogène, on étudiant l’influence de quelques paramètres comme : le pH initial de la solution, la quantité du polluant « rouge Congo », la masse de fer, la teneur de H₂O₂ et la température, ainsi l’influence de l’Ultrason sur l’accélération de la dégradation de cette substance a été suivie par spectrophotométrie UV/visible et les meilleurs résultats sont obtenus en utilisant le procédé (Fe2+/US/H₂O₂) pour la dégradation du Rouge Congo.